The performance of dual diffuser modulation using wavelength filtrate detection for free space optics in the presence of rain consequence
Free space optics (FSO) is one of the effective solutions to the ever growing needs of high speed data transfer. It offers unlicensed, higher speed with unlimited bandwidth as well as provides an excellent security. However, it is sensitive to local weather conditions which results to the inconsiderable loss of signal power over the communication path. To the fact, the quality of the FSO links are mainly affected by rain attenuation especially in a tropical environment. The conventional modulation of FSO system increases the error rate and produces low power received in situation of bad weather. Besides that, the existing detection degrades the received signal and not properly operated. Hence, in order to cater this problem, the proposed detection namely Wavelength Filtrate Detection has been developed to enhance the performance of FSO system. The proposed detection is based on the function of Fibre Bragg Grating which is capable to optimise the filter wavelength. In this research, the collection of rainfall data in year 2015 is provided by Malaysia Meteorological Department which covers region in Chuping, Perlis. From this data, a depth analysis of rain attenuation by using mathematical equation of power law has been carried out which results to the maximum rain attenuation of 13dB/km. This value is categorized under heavy rain condition. Then, the analysis is continued with the comparison between conventional modulation technique On Off Keying (OOK) and Dual Diffuser Modulation (DDM). Two types of analysis are done which are theoretical and simulation to prove that DDM technique enhances the performance of FSO system due to the adverse weather condition. The analysis continues with comparison between existing detection and Wavelength Filtrate Detection. The DDM technique is selected as the main modulation in this research because it supports 0.12km range of transceiver and improves signal received approximately 4dBm from the mathematical analysis. Also, the eye pattern in 0.5km range shows DDM technique is widely open with better BER 8.10×10-7 compares to OOK technique which is 6.51×10-4 and results to the higher loss of signal. Furthermore, this technique also supports high data rate up to 10Gbps. The problem occur in DDM technique is on the detection stage. The detection needs to be improved to avoid high signal losses when adverse weather condition occurs. To overcome this issue, Wavelength Filtrate Detection has been developed and it shows the improvement of 21% magnitude of BER as well as increase the power received up to 6dBm. As conclusion, the combination of DDM technique and Wavelength Filtrate Detection (WFD) have increase the performance of FSO system and capable to transmit high capacity of data in a situation of adverse weather condition.